Ketingting think: promoting innovative traditional game to young generation / Mahanim Omar ... [et al.] - Omar, Mahanim; Saad, Siti Mariam; Abu Mansor, Siti Nurleena (2018)
In this era, smart phones and video games are the latest fads among the younger generation to preoccupy them with modern entertainment, distraction, and technology to pass their time. However, there is that one element that seems to be missing from most of those modern games - that physical and personal human interaction which usually incorporated in Malay cultural heritage. Ketingting game is one of the heritages which is still popular nowadays. It is a game that is not only entertaining but also beneficial for mental and physical development to the players. 'Ketingting Think' is an innovation of this traditional game created to add vibrantly and creativity of this game. With a new compelling shape and colours, 'Ketingting Think' is hoped to aroused curiosity and interest among the youngsters.